How Social Responses to Child Sexual Abuse and Intimate Partner Violence Affect Homelessness Among Women in Two Rural Regions With Resource-Based Economies in Eastern Quebec. (March 2023) - Flynn, Catherine; Couturier, Pénélope; Turcotte, Simon; Dubé, Kim; Levesque, Christophe; Côté, Philippe-Benoit; Lapierre, Simon
This study presents findings from a qualitative study conducted in two relatively remote, primarily rural regions of the Canadian province of Quebec whose resource-based economic structures exacerbate inequalities between men and women. The purpose of this study was to understand how violence and homelessness intertwine in women's life courses in such regions. On the basis of past research showing that gender socialization around traditional roles and conservative values is particularly tenacious in non-urban areas, we conducted life-course interviews with 22 women in 13 different towns and villages of these two regions. Our content analysis of these interviews showed that specific social responses have forced women to maintain relationships with their aggressors or with people who have protected them, thus relegating these women's lives to the private sphere while reducing their opportunities for social participation in the public sphere. These social responses, together with women's economic and social disadvantages in these regions, were also the main factors that explain homelessness experienced by the participants in this study. Our analysis of these responses illustrates the patriarchal social structure of power in these regions, which is perpetuated in the interpersonal, institutional, and representational dimensions and keeps women in precarious, subordinate social positions, while ostracizing or punishing women who try to resist.